Cervical Spine MRI Findings in the Evaluation of Persistent Neck Pain in a Nigerian Tertiary Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Neck pain is almost as common as low back pain; however, it is under reported especially among Nigerians. Neck pain has a diverse etiology, so it poses a diagnostic dilemma.Objective:To present the pattern of magnetic resonance imaging (MRI) findings in patients with persistent neck pain in resource poor setting.Materials and Methods:A two-year retrospective review of 130 patients (age range 13 to 78 years) who were referred for cervical MRI scan due to neck pain at the radiology department of Ahmadu Bello University Teaching Hospital, Zaria. All the patients were scanned using a single Siemens (Magneto Concerto) MRI scanner. Sagittal T1-weighted and T2-weighted fast spin echo images were acquired, and axial images and contrast-enhanced studies were done only when required.Results:This study included 96 males and 34 females with a mean age, at presentation, of 48.4 (±3.6 years) and modal age group of 41–50 years. Cervical spondylosis constituted the major finding 84 (64.6%). Other causes of neck pain were tuberculosis of the cervical spine (0.8%), vitamin B12 deficiency (0.8%), and spinal neoplasm (1.5%). Cervical cord compression was seen in 69 (53.1%) patients. In a few patients [5 (3.8%)], however, no abnormality was seen on MRI.Conclusion:Cervical spondylosis is the most common cause of neck pain in our environment. MRI obviates the need for a barrage of investigations and threshold should be lowered where the modality is available and in the appropriate clinical setting.